A Scoping Review of Psychological Assessment in Mission and Ministry Candidates. Issue 1 (March 2023) - Thompson, Katherine N.; Kimber, Thomas; Williams, David; Matthews, Delle; Grossmann, Mathis; Brautigam, Michael
Missionary attrition together with the problem of institutional child sexual abuse in the Church has highlighted the importance of a standardized psychological assessment process for mission and ministry candidates. This scoping review aimed to examine peer-reviewed publications, from 2001 to 2021, which focused on the psychological assessment of ministry and cross-cultural mission candidates, to find knowledge gaps that exist. Using scoping review guidelines, 6, 739 references were identified and 2, 476 duplicates were removed. A further 4, 254 references were excluded because they did not meet screening criteria. A total of nine high-quality articles remained, together with five articles that were added based on the bibliography of these references. This scoping review found the few papers published either focused on the use of personality tests or made recommendations about how these assessments should be conducted. The studies reported that candidates for ministry and mission in US samples have normative personality profiles regardless of age or ethnicity. Other papers reviewed knowledge and opinion and highlighted the need for screening for psychosexual development and to prevent attrition in mission and ministry roles. The overall dearth of publications suggested a need for more international research into how to standardize and utilize psychological assessments.